Energetics of basic Karate Kata - Bussweiler, J.; Hartmann, U. (European Journal of Applied Physiology, 2012)
Knowledge about energy requirements during exercises seems necessary to develop training concepts in combat sport Karate. It is a commonly held view that the anaerobic lactic energy metabolism plays a key role, but this assumption could not be confirmed so far. The metabolic cost and fractional energy supply of basic Karate Kata (Heian Nidan, Shotokan style) with duration of about 30 s were analyzed. Six male Karateka [mean ± SD (age 29 ± 8 years; height 177 ± 5 cm, body mass 75 ± 9 kg)] with different training experience (advanced athletes, experts, elite athletes) were examined while performing one time and two time continuously the sport-specific movements. During Kata performance oxygen uptake was measured with a portable spirometric device, blood lactate concentrations were examined before and after testing and fractional energy supply was calculated. The results have shown that on average 52 % of the energy supply for one Heian Nidan came from anaerobic alactic metabolism, 25 % from anaerobic lactic and 23 % from aerobic metabolism. For two sequentially executed Heian Nidan and thus nearly doubling the duration, the calculated percentages were 33, 25 and 42 %. Total energy demand for one Kata and two Kata was approximately 61 and 99 kJ, respectively. Despite measured blood lactate concentrations up to 8.1 mmol l-1, which might suggest a dominance of lactic energy supply, a lactic fraction of only 17-31 % during these relatively short and intense sequences could be found. A heavy use of lactic energy metabolism had to be rejected.